The Symbolic Essence of “Seserahan”: Exploring the Communication Message in The Marriage Procession of the Clan - Zainal, Anna Gustina; Pahreza, Urba; Aryanti, Nina Yudha; Kagungan, Dian; Meutia, Intan Fitri (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study aims to decode the symbolic communication conveyed through offerings during the Besagh arrival procession in the wedding customs of the Mesuji Lampung clan residing in Banjar Margo, Tulang Bawang District, Lampung Province. Although numerous studies have highlighted the role of offerings in Indonesian wedding cultures, there is a notable research gap regarding the symbolism within the Besagh procession of the Mesuji Lampung clan. This research is important as it reveals the traditional values and local wisdom embodied in the offerings, strengthening the community's social and familial bonds. The theoretical framework of symbolic communication is employed to analyze the meanings embedded in the offerings. Conducted qualitatively in Banjar Margo District, the study uses Snowball Sampling to select informants. Data gathered from these informants were analyzed through an interpretive approach to derive deep insights into the symbolic meanings of each offering. Offerings, integral to wedding processions across Indonesian cultures, symbolize the commitment and involvement of both parties. Families express values, aspirations, and social relations between clans through these offerings. For instance, kemingan (mat) symbolizes simplicity and blessings in the household, while lemang (glutinous rice) signifies unity and the strength of marital bonds. Using traditional materials honors tradition and reinforces familial and communal ties. Thus, this study reveals how traditional materials in the Besagh procession convey respect, prayers, and blessings from extended families to the prospective couple, reflecting unity, loyalty, prosperity, and respect within marriage.